2019
DOI: 10.3839/jabc.2019.059
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polyphenolic metabolites from Artemisia gmelinii Weber ex Stechm. and regional comparison in Korea

Abstract: Artemisia species are widely used as food ingredients and raw material in traditional medicine. However, to date, the secondary metabolites of Artemisia gmelinii Weber ex Stechm. have not been sufficiently investigated. The secondary metabolites of A. gmelinii, which was collected from representative regions in Chungbuk, Gangwon, and Gyeongbuk, were analyzed using ultraperformance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTof MS) combined with an unsupervised principal component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several studies have reported that fermentation increases the anti-aging activity of products [34,35]. Jang, Kim et al [34] reported greater values for fermented Trapa japonica fruit than for protein extracted from fresh fruit.…”
Section: Anti-aging Inhibitory Activitiesmentioning
confidence: 99%
“…Several studies have reported that fermentation increases the anti-aging activity of products [34,35]. Jang, Kim et al [34] reported greater values for fermented Trapa japonica fruit than for protein extracted from fresh fruit.…”
Section: Anti-aging Inhibitory Activitiesmentioning
confidence: 99%
“…The tentative identification of peak 2 was pseudolaroside A. The second-order spectrum of peak 3 had a characteristic fragment ion at m/z 163[hydroxycinnamic acid-H] − [ 20 ]. Peak 3 was confirmed tentatively as melilotoside.…”
Section: Resultsmentioning
confidence: 99%